STUDENTS’ REFLECTIVE THINKING IN MATHEMATICAL PROBLEM SOLVING - Rijalush Sholikhin; Dian Septi Nur Afifah; Maryono Maryono (MaPan : Jurnal Matematika dan Pembelajaran, 2021)
This study aims to describe reflective thinking in solving mathematical problems on linear equations system with three variables based on mathematical abilities. This study uses a qualitative approach with case study type. The instruments in this study used tests and interviews. The subjects of this study came from 38 students grade X Natural Science 2 Islamic Senior High School 3 Blitar, taken one from each category of students with high, moderate, and low mathematical ability to be the subject of research. The data analysis techniques used are data reduction, data display, and conclusions drawing/verification. The validity test of data used persistent observation and triangulation. The research results obtained by students with high and moderate abilities can meet the phase of reacting, comparing, and contemplating in reflective thinking. Meanwhile, low mathematical ability students are only able to meet the reacting and comparing phases.